(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The article presents a comparative study of the genre features of English and Uzbek drama through the works of Richard Brinsley Sheridan and Erkin Vohidov. The research aims to identify the similarities and differences in the genre structure, stylistics, and thematic focus of classical English comedies and contemporary Uzbek drama. Particular attention is paid to the construction of characters, plot development, and the use of comedic and dramatic techniques. The study also explores the influence of historical, social, and cultural contexts on the formation of genre in both national traditions. The results reveal both universal patterns and distinctive national features in the representation of social and moral issues through drama. This research has practical significance for literature teaching, theatrical productions, intercultural communication, and comparative literary studies.